Socioeconomic position and use of hospital-based care towards the end of life: a mediation analysis using the English Longitudinal Study of Ageing - Joanna M Davies, MSc; Matthew Maddocks, PhD; Kia-Chong Chua, PhD; Panayotes Demakakos, PhD; Katherine E Sleeman, ProfPhD; Fliss E M Murtagh, ProfPhD (Elsevier, 2021)
Summary: Background: Many patients prefer to avoid hospital-based care towards the end of life, yet hospitalisation is common and more likely for people with low socioeconomic position. The reasons underlying this socioeconomic inequality are not well understood. This study investigated health, service access, and social support as potential mediating pathways between socioeconomic position and receipt of hospital-based care towards the end of life. Methods: For this observational cohort study, we included deceased participants from the nationally representative English Longitudinal Study of Ageing of people aged 50 years or older in England. We used a multiple mediation model with age-adjusted and gender-adjusted probit regression to estimate the direct effect of socioeconomic position (measured by wealth and education) on death in hospital and three or more hospital admissions in the last 2 years of life, and the indirect effects of socioeconomic position via three mediators: health and function, access to health-care services, and social support. Findings: 737 participants were included (314 [42·6%] female, 423 [57·4%] male), with a median age at death of 78 years (IQR 71-85). For death in hospital, higher wealth had a direct negative effect (probit coefficient −0·16, 95% CI −0·25 to −0·06), which was not mediated by any of the pathways tested. For frequent hospital admissions, health and function mediated the effect of wealth (−0·04, −0·08 to −0·01), accounting for 34·6% of the total negative effect of higher wealth (−0·13, −0·23 to −0·02). Higher wealth was associated with better health and function (0·25, 0·18 to 0·33). Education was associated with the outcomes only indirectly via wealth. Interpretation: Our findings suggest that worse health and function could partly explain why people with lower wealth have more hospital admissions, highlighting the importance of socioeconomically driven health differences in explaining patterns of hospital use towards the end of life. The findings should raise awareness about the related risk factors of low wealth and worse health for patients approaching the end of life, and strengthen calls for resource allocation to be made on the basis of health need and socioeconomic profile. Funding: Dunhill Medical Trust Fellowship Grant (RTF74/0116).